A Framework for Automatically Generating Interactive Instructional Scaffolding - O’Rourke, Eleanor; Andersen, Erik; Gulwani, Sumit; Popović, Zoran (CHI '15 Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems, Seoul, Republic of Korea, 2015)
Interactive learning environments such as intelligent tutoring systems and software tutorials often teach procedures with step-by-step demonstrations. This instructional scaffolding is typically authored by hand, and little can be reused across problem domains. In this work, we present a framework for generating interactive tutorials from an algorithmic representation of the problem-solving thought process. Given a set of mappings between programming language constructs and user interface elements, we step through this algorithm line-by-line to trigger visual explanations of each step. This approach allows us to automatically generate tutorials for any example problem that can be solved with this algorithm. We describe two prototype implementations in the domains of K-12 mathematics and educational games, and present results from two user studies showing that educational technologists can author thought-process procedures and that generated tutorials can effectively teach a new procedure to students.